Developing an English proficiency program for science, mathematics and English teachers - Go, Romeleen S. (2007)
The study aimed to select, adapt, and organize materials and activities, and to arrive at a proficienct language program responsive to the language needs of the teachers. The researcher-developed language program used a combination of instruction models, content-based and task-based instruction with Academic English as its backbone. The study employed a combination of descriptive analysis of data and hypothesis testing to determine whether the program has an effect in the different language variables. The results of the secondary and primary sources of data verified that the language proficiency program was responsive in catering to the language needs of the teachers of science, math, and English.